Dualisme Penerapan Hukum Bagi Pelaku Kekerasan Seksual Terhadap Anak di Provinsi Aceh - amarina habibi (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
Act Number 35, 2014 on Child Protection (UUPA) and Qanun (provincial law) Aceh Number 6, 2014 regarding Qanun Jinayat has given rise to legal dualism. Both laws and regulations govern the same case in the jurisdiction of Aceh, so that it can cause problems in its enforcement. This research applies primary, secondary and tertiary legal sources. This research uses the statue approach. Library research data are then analyzed from secondary and tertiary legal sourcesby using deductive method.The research shows that the enforcement of absolute power at the judicial institutions relating the trial of the sexual offence towards children cases in Aceh, the Public Court, which is granted its power under the UUPA,is privilege compared to Syar’iyah Court, which is having its power from Qanun Jinayat. The reasons for this are as following: a) the punisment in the UUPA is more serious and cumulative, while in Qanun Jinayat is more lenient and alternative; b) UUPA regulates specific things regarding child cases, while Qanun Jinayat is general; c) the enforcement of UUPA together with its changes is still facing hurdles, and there is also the enactment of Qanun Jinayat; d) there are problems in regards with lack of facilities of the detentions and budget during the process of the cases and there is an absent of the cooperation between correctional center for the convicted under the Qanun Jinayat; e) judges in the Public Court mostly already have certificates in dealing with child case compared to Syar’iyah Court. This research found that the later court judges have not had any certificate yet. The enforcement of punishment towards the perpetrators in Aceh mostly tried under the UUPA compared to using Qanun Jinayat as it provides more justice for victims.